Knowledge expectations of surgical orthopaedic patients: a European survey - Valkeapaa, Kirsi; Klemetti, Seija; Cabrera, Esther; Cano, Sara; Copanitsanou, Panagiota P.; Ingadottir, Brynja; Istomina, Natalja; Johansson Stark, Asa; Katajisto, Jouko K.; Lemonidou, Chryssoula; Sigurdardottir, Árun K.; Sourtzi, Panayota A.; et al. (My University, 2014)
Ageing population entails a growing international problem of osteoarthritis. Best practices for education of these patientsare lacking. This study focused on empowering education in Northern (Finland, Iceland, Lithuania and Sweden) andSouthern Europe (Cyprus, Greece and Spain). The aim was to analyse associations between expected knowledge andbackground factors. The data were collected from European arthroplasty patients with the Knowledge Expectations ofhospital patients- scale, (KEhp- scale), including bio-physiological, functional, experiential, ethical, social and financialdimensions. Patients had essential bio-physiological and functional knowledge expectations. Women expected more thanmen, employed less than retired, unemployed or who worked at home. Generally, patients in Northern countriesexpected more than in Southern countries. However, highest expectations were found in Sweden and Greece, lowest inSpain and Cyprus. There are differences in knowledge expectations based on patients’ backgrounds. Development ofcommon standards in European patient education needs further research.
Keywords: Empowering patient education; Knowledge expectations; Orthopaedics